Synergistic Role of Bacterial Urease and Carbonic Anhydrase in Carbonate Mineralization - Dhami, N.; Reddy, M.; Mukherjee, Abhijit (Humana Press, 2014)
The investigation on the synergistic role of urease (UA) and carbonic anhydrase (CA) in biomineralization of calcium carbonate in Bacillus megaterium suggested that the precipitation of CaCO3 is significantly faster in bacterial culture than in crude enzyme solutions. Calcite precipitation is significantly reduced when both the enzymes are inhibited in comparison with those of the individual enzyme inhibitions indicating that both UA and CA are crucial for efficient mineralization. Carbonic anhydrase plays a role in hydrating carbon dioxide to bicarbonate, while UA aids in maintaining the alkaline pH that promotes calcification process.